Teacher's Agency and the Cooperation With Entrepreneurs in Entrepreneurship Education - Piia Kolho; Anu Raappana; Sanna Joensuu-Salo; Timo Pihkala (European Research Network Vocational Education and Training (VETNET), 2023)
Purpose: Vocational education and training (VET) in Finland takes place more and more at workplaces. Hence, the teachers' cooperation with companies has become important. Little research has been done on the teacher's activities in business cooperation and the factors affecting business cooperation. The teacher's decisions and choices are made possible through the teacher's autonomy and agency. The teacher's agency is understood as a capacity to utilise autonomy. In this study, the teacher's agency is reflected in their activity in developing entrepreneurial learning environments and activity in developing regional entrepreneurship education (EE). The study was conducted among Finnish VET teachers. In Finland EE is understood in its broad sense and the teacher is in a significant position choosing where, how and with whom they implement EE. The main research question in this article is: How does the VET teacher's agency in EE affect their cooperation with entrepreneurs?  Methods: The data consists of 933 vocational teachers' responses. An open online survey tailored for teachers was used in the data collection (Measurement Tool for Entrepreneurship Education). Ordinal regression analysis has been used to analyse the data. Results: The teacher's agency is a significant factor explaining his/her level of cooperation with entrepreneurs. The results show that the teacher's activity, desire, and ability to express agency, strengthens the use of companies in teaching. Surprisingly, the teacher's personal entrepreneurial background and the number of companies in the area do not act as explanatory factors for entrepreneurs' cooperation. The study makes several suggestions on teachers' perceptions of the factors explaining and creating agency as an entrepreneurship educator.  Conclusions: In Finland, teachers' autonomy is high. Teachers have the freedom to utilise their agency in many ways. They can, for example, make their own decisions and renew their teaching in many ways if they are willing and encouraged to do so. It seems like the question is more about management and teacher identity. The teacher's agency should be strengthened, and the teacher should be given the option to act more freely. Furthermore, the teacher's autonomy is not enough; agency is also needed.